A clinical competence approach to examine British and Finnish nurses' attitudes towards the rapid response system model: A study in two acute hospitals. Issue 1 (January 2022) - Azimirad, Mina; Magnusson, Carin; Wiseman, Allison; Selander, Tuomas; Parviainen, Ilkka; Turunen, Hannele
Abstract: Background: Nurses' clinical competence involves an integration of knowledge, skills, attitudes, thinking ability, and values, which strongly affects how deteriorating patients are managed. Objectives: The aim of the study was to examine nurses' attitudes as part of clinical competence towards the rapid response system in two acute hospitals with different rapid response system models. Methods: This is a comparative cross-sectional correlational study. A modified "Nurses' Attitudes Towards the Medical Emergency Team" tool was distributed among 388 medical and surgical registered nurses in one acute hospital in the UK and one in Finland. A total of 179 nurses responded. Statistical analyses, including exploratory factor analysis, Mann–Whitney U tests, Kruskal–Wallis tests, chi-square tests, and univariate and multivariate regression analyses, were used. Findings: Generally, nurses had positive attitudes towards rapid response systems. British and Finnish nurses' attitudes towards rapid response system activation were divided when asked about facing a stable (normal vital signs) but worrisome patient. Finnish nurses relied more on intuition and were more likely to activate the rapid response system. Approximately half of the nurses perceived the physician's influence as a barrier to rapid response system activation. The only sociodemographic factor that was associated with nurses activating the rapid response system more freely was work experience ≥10 years. Conclusions: The findings are beneficial in raising awareness of nurses' attitudes and identifying attitudes that could act as facilitators or barriers in rapid response system activation. The study suggests that nurses' attitudes towards physician influence and intuition need to be improved through continuing development of clinical competence. When the system model included "worrisome" as one of the defined parameters for activation, nurses were more likely to activate the rapid response system. Future rapid response system models may need to have clear evidence-based instructions for nurses when they manage stable (normal vital signs) but worrisome patients and should acknowledge nurses' intuition and clinical judgement.